1999
DOI: 10.1044/jslhr.4206.1378
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of Individual Muscles to the Submental Surface Electromyogram During Swallowing

Abstract: Submental surface electromyographic recordings are commonly used in the investigation of swallowing disorders. The measured electromyography is thought to reflect the actions of floor-of-mouth muscles. Although this is a reasonable assumption, to date there have been no investigations to delineate which muscles contribute to this surface recording. The primary goal of this experiment was to determine which muscles contribute most to the submental surface. Electromyography was recorded simultaneously from the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
69
1
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(73 citation statements)
references
References 16 publications
1
69
1
2
Order By: Relevance
“…The electromyographic signal captured in the submental region reflects the activity of the mylohyoid, geniohyoid and anterior digastric belly muscles, with small contribution of the genioglossus one (13) . There is a great intercorrelation among the suprahyoid muscles and it is not possible to capture, with surface electrodes, the electrical activity of only one of them.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The electromyographic signal captured in the submental region reflects the activity of the mylohyoid, geniohyoid and anterior digastric belly muscles, with small contribution of the genioglossus one (13) . There is a great intercorrelation among the suprahyoid muscles and it is not possible to capture, with surface electrodes, the electrical activity of only one of them.…”
Section: Discussionmentioning
confidence: 99%
“…Because it represents the activity of suprahyoid muscles, the electromyographic assessment of the submental region is commonly performed in the investigation of swallowing disorders (11,12) . In the submental electromyographic assessment, it is obtained the electrical activity of mylohyoid, anterior belly of the digastric and geniohyoid muscles (13) . Authors compared the electrical activity of the suprahyoid musculature in the tongue pressure exercises against the palate and head elevation from the supine position, and greater submental electrical activity was obtained during the pressure exercise of the tongue on the palate (11) .…”
Section: Introductionmentioning
confidence: 99%
“…The examination captures the potentials of action generated in muscular contractions and allows the comparison of these values in relation to the amplitude and duration of the movement [21][22][23][24][25] . The suprahyoid muscles play an important role during swallowing because they are involved in the laryngeal elevation 26 . One study found that the increased tongue pressure against the palate coincided with increased suprahyoid muscle activity 26 , suggesting that tongue pressure exercises on the palate are indicated to strengthen not only the intrinsic musculature of the tongue, but also of the supra-hyoid muscles, improving airway protection during swallowing in patients with dysphagia.…”
Section: Introductionmentioning
confidence: 99%
“…The suprahyoid muscles play an important role during swallowing because they are involved in the laryngeal elevation 26 . One study found that the increased tongue pressure against the palate coincided with increased suprahyoid muscle activity 26 , suggesting that tongue pressure exercises on the palate are indicated to strengthen not only the intrinsic musculature of the tongue, but also of the supra-hyoid muscles, improving airway protection during swallowing in patients with dysphagia. Thus, some studies use surface EMG of the suprahyoid musculature to compare tongue strength training exercises used in the clinical practice of dysphagia 21,22,24 .…”
Section: Introductionmentioning
confidence: 99%
“…A larger size of sample often results in a longer period of oral processing, larger number of chewing, and higher EMG amplitude (Dantas and Dodds, 1990;Palmer et al, 1999;Miyawaki et al, 2000;Kohyama et al, 2005bKohyama et al, , 2007aWoda et al, 2006;Miyaoka et al, 2010;Ashida et al, 2010). We compared EMG variables during free eating of rice gruel (5 g and 10 g), and found that 10 g gruel exhibited significantly higher EMG variables corresponding to mastication time such as number of chews, chewing time, and total muscle activity than 5 g. However there were no significant differences between 5 g and 10 g in EMG variables per chew such as EMG amplitude, duration, muscle activity or muscle work, and chewing cycle (Kohyama and Nakayama, 2004).…”
Section: Introductionmentioning
confidence: 99%